The Relationship between Maternal Perinatal Depression and Offspring Depression: A Meta-Analysis - Qing Yang; Wei Mi; Fang Su; Wei Song (Clinical and Experimental Obstetrics & Gynecology)
Background: Antepartum depression, with an incidence of 20.7%, is a pressing global public health concern due to its detrimental effects on both the physical and mental health of pregnant women, as well as the potential risk it poses for depression in their offspring. Nevertheless, there is a lack of consensus among existing studies regarding this issue. Here, we systematically evaluated the relationship between maternal perinatal depression and offspring depression by meta-analysis. Methods: We conducted a comprehensive search for relevant studies in Pubmed, Embase, The Cochrane Library, CNKI, Wanfang, VIP, and Chinese Biomedical Literature Service System databases. The prospective cohort studies, which were published in English or Chinese, reported the occurrence of maternal prenatal and/or postnatal depression within one year postpartum and assessed the subsequent development of depression in their offspring, were included. Study quality was assessed with the Newcastle-Ottawa Scale. Review Manager 5.4 software was used for meta-analysis. Subgroup analysis was performed. Publication bias was evaluated with a funnel plot. Results: Totally, 12 studies were included. The meta-analysis found that maternal perinatal depression increased the risk of offspring depression by 1.64 (95% confidence interval (95% CI): 1.37, 1.96, p < 0.001). Subgroup analysis showed that the risk of offspring depression was significantly increased in the European population with maternal perinatal depression (odds ratio (OR) = 1.90, 95% CI (1.49, 2.42), p < 0.001), but not in the Australian and the American populations. The combined effect sizes of maternal antepartum and postpartum depression were (OR = 1.70, 95% CI (1.27, 2.27), p < 0.001) and (OR = 1.74, 95% CI (1.31, 2.32), p < 0.001), respectively. The combined effect size of the relationship of maternal perinatal depression with offspring depression in childhood and adulthood was (OR = 1.70, 95% CI (1.28, 2.25), p < 0.001) and (OR = 1.60, 95% CI (1.27, 2.02), p < 0.001), respectively. The adjusted and unadjusted combined effect sizes were (OR = 1.44, 95% CI (1.14, 1.82), p < 0.001) and (OR = 1.97, 95% CI (1.49, 2.60), p < 0.001), respectively. There may be some publication bias in the included studies. Conclusions: Maternal perinatal depression is associated with an increased risk of depression in offspring. Effective prevention and management of depression in perinatal women is necessary to mitigate the risk of depression in offspring.